2007
DOI: 10.1080/10401230701333038
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Complications of Interferons: Classification, Neurochemical Bases, and Management

Abstract: Interferon-treated patients should be monitored for mental status changes. There are no controlled studies on pharmacological management of interferon-induced neuropsychiatric side effects. The use of interferons in patients with stable psychiatric disorders is not contraindicated. However, such patients should be closely monitored during the course of treatment with interferons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 90 publications
0
18
0
1
Order By: Relevance
“…Symptoms similar to but not meeting the criteria of full delirium have long been recognized in people treated with recombinant IFN [88] and occurrence of sub-syndromal delirium has been associated with adverse outcomes in elderly individuals [27]. In healthy human subjects experimental treatment with bacterial endotoxin produces a dose-dependent effect in cognitive function, emotional state and sleep [96,110].…”
Section: Reactions Of Cns Mediated By Molecules From Systemic Circulamentioning
confidence: 99%
“…Symptoms similar to but not meeting the criteria of full delirium have long been recognized in people treated with recombinant IFN [88] and occurrence of sub-syndromal delirium has been associated with adverse outcomes in elderly individuals [27]. In healthy human subjects experimental treatment with bacterial endotoxin produces a dose-dependent effect in cognitive function, emotional state and sleep [96,110].…”
Section: Reactions Of Cns Mediated By Molecules From Systemic Circulamentioning
confidence: 99%
“…Review of literature has shown that persons with disabilities are more likely than others to experience mental health problems due to the psychological burden associated with the condition and/or the effects of the medications that are being used to suppress the disabling condition [24,28]. Also, mental disorders may share common risk factors with other health conditions and disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that having been exposed to mood disorders in the past and carrying G allele variation of 5-hydroxytryptamine receptor 1-A (HTR1-A) significantly influenced the increase in IFN-induced depression [27]. Besides, reduced glucocorticoid negative feedback sensitivity leading to flattening of the diurnal cortisol slope [28], direct effect on central serotonin neurotransmission [29][30][31][32], activation of indoleamine 2,3-dioxygenase which indirectly converts tryptophan to kynurenine [33], and a decrease in the levels of brain-derived neurotrophic factor after IFN treatment might have played a role in the etiology of IFN-induced depression [34]. These associations are outside the scope of this study.…”
Section: Discussionmentioning
confidence: 99%